2007
DOI: 10.2105/ajph.2005.073411
|View full text |Cite
|
Sign up to set email alerts
|

REAL Men: A Group-Randomized Trial of an HIV Prevention Intervention for Adolescent Boys

Abstract: The study demonstrates that fathers can serve as an important educator on HIV prevention and sexuality for their sons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
156
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(160 citation statements)
references
References 17 publications
1
156
1
2
Order By: Relevance
“…Evidence-based interventions have successfully strengthened relationships between black fathers and sons in other settings 18,28 ; similar programs may provide a promising direction for future health-promotion efforts with YBMSM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence-based interventions have successfully strengthened relationships between black fathers and sons in other settings 18,28 ; similar programs may provide a promising direction for future health-promotion efforts with YBMSM.…”
Section: Discussionmentioning
confidence: 99%
“…27 Furthermore, communication is amenable to augmentation through public health interventions; a father-son intervention improved levels of paternal communication about sex, leading to increased abstinence in a predominantly black sample. 28 Further analyses in the same cohort suggested that this relationship between father-son communication and sexual risk reduction was mediated by increases in the sons' self-efficacy for abstinence. 29 Other studies, however, have found null or even negative effects of father-son communication on sexual risk behaviors and attitudes, 26 suggesting that such communication is highly variable (e.g., in terms of timing, tone, and content) and may have heterogeneous effects on behavior as a result.…”
Section: Communication About Sexmentioning
confidence: 95%
“…45,46,[48][49][50][51] Because of heterogeneity in how this communication domain was defined (ie, number of new topics discussed, repeated topics, individual topics discussed, percentage of topics discussed, mean number of topics discussed, and percentage that reported lower scores from scale measures), it is difficult to summarize the findings. In general, parents reported an increase in the content of communication, whereas adolescent reports were highly varied.…”
Section: Content Of Discussionmentioning
confidence: 99%
“…[44][45][46][47][48][49][50][51] The studies were published in 11 journals that represent a variety of disciplinary fields including psychology, 46,50,52 family relations, 44,53,54 adolescent health, 47,55 general medicine, 51 public health, 48 nursing, 56 and sexual health. 49 …”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation